Intentions to Stop Drinking Among Adolescents in One Area - Park, Min-Hee (Advances in Social Sciences Research Journal, 2022)
This study was to investigate the intention of drinking cessation among adolescents in a certain area. In order to investigate the intention to stop drinking, the ‘non-drinking intention during adolescent’, the ‘drinking refusal intention’, and the ‘lifetime non-drinking intention’ were investigated, and the differences by gender and school were analyzed. Two samples t-test and F-test were used to analyze the results of this data. As a result of this study, it was found that the intention to stop drinking decreased as the school level increased. It is necessary to maintain continuous recognition about drinking, and it is necessary to improve the socially acceptable atmosphere for drinking.